Hyaluronic Acid Dipeptide Gels Studied by Raman Spectroscopy - Vlasta Mohaček-Grošev; Jože Grdadolnik (Crystals)
This study presents a detailed Raman spectroscopic investigation of hydrogels composed of sodium hyaluronate and two N-terminally blocked dipeptides: N-acetyl-L-alanine-methyl-amide (NAcAlaNHMA) and N-acetyl-L-tyrosine-methyl-amide (NAcTyrNHMA). Vibrational spectra of the dipeptides in both crystalline and aqueous forms were analyzed and supported by density functional theory (DFT) calculations. Spectral features of the hyaluronan component were elucidated by simulating the vibrational modes of its two principal disaccharide building blocks. Gels were prepared with varying dipeptide-to-hyaluronan ratios, and their structural characteristics were examined using Raman spectroscopy and atomic force microscopy. The results showed that while NAcAlaNHMA exhibited no significant interaction with the HA matrix, NAcTyrNHMA demonstrated specific binding behavior, as evidenced by notable shifts in its N–H and C–O–H vibrational bands. These findings indicate that NAcTyrNHMA binds to hyaluronic acid via hydrogen bonding, likely involving carboxyl and hydroxyl functional groups. This study highlights the potential for selective tuning of HA-based hydrogels using dipeptides, with implications for biomedical applications such as drug delivery, antimicrobial gels and biomaterial design.